Exploring Willingness to Communicate among Master's Students Majoring in English Education: What Makes it Different? - Nurfitriana, Latifah; Basthomi, Yazid; Khoiri, Niamika El (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study investigates the Willingness to Communicate (WTC) among Indonesian master's students in an English Education program, addressing a significant gap in the literature that has traditionally focused on high school and undergraduate levels. Understanding WTC at the graduate level is crucial, as these students are often expected to demonstrate advanced language skills and effective communication in professional contexts. By focusing on graduate students, this research aims to explore the level of WTC among Indonesian masterâ€™s students majoring in English education and the factors that influence it.Â Employing a mixed-methods approach, data were collected from students at a public university in East Java using a questionnaire and semi-structured interviews.Â Findings reveal that these students exhibit a high level of WTC, largely driven by self-confidence, low anxiety, and strong motivation. The study highlights the significant role of early language learning experiences and supportive learning environments in shaping WTC. Despite its contributions, limitations include a small sample size and a short data collection period, which may impact the generalizability. The implications of this research suggest the need for more tailored pedagogical strategies that enhance communicative confidence in advanced language learners, with recommendations for future research focusing on larger, longitudinal studies.